Dynamic Ag+-intercalation with AgSnSe2 nano-precipitates in Cl-doped polycrystalline SnSe2 toward ultra-high thermoelectric performance. Issue 16 (1st April 2019) - Liu, Chengyan; Huang, Zhiwei; Wang, Dianhui; Wang, Xiuxia; Miao, Lei; Wang, Xiaoyang; Wu, Shaohai; Toyama, Nozomu; Asaka, Toru; Chen, Junliang; Nishibori, Eiji; Zhao, Li-Dong
Abstract : Thermally driven Ag + -intercalation into the van der Waals gap results in a record thermoelectric performance in polycrystalline SnSe2 . Abstract : Recently, thermoelectric lead-free selenides have attracted great attention due to their earth-abundant, low-cost and environment-friendly characteristics. Here we report a new strategy to simultaneously enhance the electronic transport properties and reduce the thermal conductivity of polycrystalline SnSe2 . By combining weak van der Waals bonding with the mobile behavior of Ag + ions, the carrier concentration is optimized over a wide temperature range, which can be attributed to the dynamic Ag + -intercalation into the van der Waals gap from the Ag + ion reservoir AgSnSe2 . On account of additional electrical bridges between interlayers contributed by the intercalated Ag + ions and weak anisotropy, an exciting high power factor of up to ∼7.46 μW cm −1 K −2 at 789 K is achieved along the pressing direction. In addition, the thermal conductivity is simultaneously reduced to ∼0.57 W m −1 K −1 at 789 K, owing to numerous line defects, phase interfaces, twin boundaries, dislocations and intercalated atomic layers generated after Ag introduction, as well as the anharmonic vibration of Ag + ions. As a result, a record peak ZT of ∼1.03 at 789 K is realized along the pressing direction, which is ∼1.6 times larger than the highest reported value (0.63) of polycrystalline SnSe2 and even comparable to that of p-type polycrystalline SnSe. This study opens a new way to achieve ultra-high thermoelectric performance, especially in layered materials.